Free help with homework

Why join Brainly?

  • ask questions about your assignment
  • get answers with explanations
  • find similar questions


Let X = -a
= -a×(-a)+3a (-a)+k=0
= a+(-3a)+k=0
= 2a+k=0
1K= 2a+0
1K= 2a
K+a= 2-1
K+a= 1
a= 1K
K = a
Hence Proved
0 0 0
sorry wrong Answer
Ok I'll try to do that
its right answer is k=2a*a
The Brain
  • The Brain
  • Helper
Not sure about the answer?
Learn more with Brainly!
Having trouble with your homework?
Get free help!
  • 80% of questions are answered in under 10 minutes
  • Answers come with explanations, so that you can learn
  • Answer quality is ensured by our experts